Entrepreneurial Bricolage in SMEs: Exploring the Interplay of Divergent Thinking, Self-Efficacy, and Gender Dynamics - De Silva, D.C.H.; Perera, M.H.D.N.; Gunawardane, H.N.R.; Liyanage, P.T.D. (Faculty of Management Studies and Commerce University of Sri Jayewardenepura, 2024)
This study investigates the relationships between divergent thinking, self-efficacy, and entrepreneurial bricolage in Small and Medium-sized Enterprises (SMEs), with a particular focus on the moderating role of gender. The high failure rate of SMEs highlights the need for a deeper understanding of these factors to enhance entrepreneurial success and sustainability. The study employed a mixed-methods approach, analyzing data from a diverse sample of SMEs to explore how cognitive processes and gender dynamics influence entrepreneurial activities. The findings reveal a significant relationship between divergent thinking and entrepreneurial bricolage, underscoring the importance of creative problem-solving in the entrepreneurial process, especially in resource-constrained environments. Self-efficacy was also found to be a key determinant of entrepreneurial success, influencing risk-taking and perseverance in the face of challenges. Notably, the study highlights the critical role of gender, with the observed gender disparity (74% males and 26% females) in the sample reflecting broader trends in entrepreneurship and pointing to different experiences and challenges faced by male and female entrepreneurs. The study's implications extend to the development of targeted support and interventions for SMEs. Understanding the roles of cognitive factors and the influence of gender can inform the design of training programs, mentorship schemes, and policy initiatives aimed at enhancing entrepreneurial skills and capabilities. The research contributes to the growing body of knowledge on the factors influencing entrepreneurship and offers practical insights for fostering a more inclusive and resilient entrepreneurial ecosystem. However, the study is not without limitations, including the sample's gender imbalance and focus on specific types of SMEs, which may affect the generalizability of the findings. Future research should aim for a more balanced gender representation and a broader range of business types and stages. This study lays the groundwork for further exploration into the complex dynamics of entrepreneurship, emphasizing the need for creativity, confidence, and inclusivity in supporting the growth and sustainability of SMEs in the global economy.
Keywords: Entrepreneurial Bricolage, SMEs, Self-Efficacy, Gender, Divergent Thinking